THE IMPLEMENTATION OF MIND MAPPING IN TARKIB LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES - Rasmuin Rasmuin; Dzurrotun Nafisah (STAI Hubbulwathan Duri, 2019)
The goal of this research is to describe the extent of the mind map methode influences. Mind map is a graphical way to represent ideas and concept, in this study mind map used in improving the student’s understanding of tarkib . With the subject of class VII C of Islamic Junior High School Batu East Java.The types of this research is classroom action research where the researcher used the Kemmis and MC Taggart model in this research with two cycles and each cycle there are 4 (four) stages were Palnning, Acting, Observing and Reflecting. Methode that used a qualitative approach. The instrument that used ini this research were observation, documentation, interview, and test. The technique of data analysis in this researrh is a descriptive analysis. The result of thisresearch showed that the completeness of student learning outcomes in the first cycle reached an average 63,63 and in the second cycle reached an average 76,06. These data have shown that in the first cycle the indicators of success have not been achieved and in the second cycle student learning outcomes have shown that indicators of success have been achieved.